2016
DOI: 10.18632/oncotarget.8116
|View full text |Cite
|
Sign up to set email alerts
|

Transmembrane adaptor protein PAG1 is a novel tumor suppressor in neuroblastoma

Abstract: (NB) is the most common extracranial pediatric solid tumor with high mortality rates. The tyrosine kinase c-Src has been known to play an important role in differentiation of NB cells, but the mechanism of c-Src regulation has not been defined. Here, we characterize PAG1 (Cbp, Csk binding protein), a central inhibitor of c-Src and other Src family kinases, as a novel tumor suppressor in NB. Clinical cohort analysis demonstrate that low expression of PAG1 is a significant prognostic factor for high stage diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 31 publications
3
14
0
Order By: Relevance
“…A defect in differentiation, together with increased activity of total SFKs we observed in cells expressing PAG1 TM- (Figure 1) is consistent with previous observations that PAG1 acts as a tumor suppressor in neuroblastoma cells (Agarwal et al, 2016;Oneyama et al, 2008). Oneyama et al (2008) first demonstrated the interaction between PAG1 and SRC.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…A defect in differentiation, together with increased activity of total SFKs we observed in cells expressing PAG1 TM- (Figure 1) is consistent with previous observations that PAG1 acts as a tumor suppressor in neuroblastoma cells (Agarwal et al, 2016;Oneyama et al, 2008). Oneyama et al (2008) first demonstrated the interaction between PAG1 and SRC.…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with our soft agar assay data (Figure 3), cells lacking PAG1 formed almost 20 times as many colonies as those re-expressing functional PAG1 in colony transformation assays (Oneyama et al, 2008). Using siRNA knockdown of PAG1, Agarwal et al also demonstrated increased SFK activity, increased anchorage independent growth, and increased ERK activity in neuroblastoma cell lines (Agarwal et al, 2016). A PAG1 mutant that lacked residues required for lipid raft localization failed to suppress SRC-mediated transformation (Oneyama et al, 2008), which emphasizes the importance of membrane localization of PAG1 for regulation of SFK activity.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Orthotopic neuroblastoma xenografts were generated in four to six week old female athymic immunodeficient NCr nude mice as previously described31. Briefly, 1 × 10 6 human SH-SY5Y neuroblastoma cells were surgically implanted in beneath the renal capsule.…”
Section: Methodsmentioning
confidence: 99%
“…Cbp could function as both a positive and negative regulator of mast cell signaling, depending upon the signaling pathway involved (Draberova et al, 2014). Cbp also serves as a central inhibitor of c-Src and other Src family kinases, as a novel tumor suppressor in neuroblastoma (Agarwal et al, 2016). Previously, we have studied the interaction of Csk L-SH2 with Cbp peptide using L-SH2 sample with and without binding with Cbp peptide (Liu and Cowburn, 2016).…”
mentioning
confidence: 99%